Turn on thread page Beta

proving composite function is injective if all it's constituent parts are injective watch

    • Thread Starter
    Offline

    15
    ReputationRep:
    I have so far

    I claim that the composition of injective functions is injective. Recall that injective means that \forall x,y \in \mathbb R , f(x)=f(y) \Rightarrow x=y.
    Let f(g(x))=f(g(y)) then using the definition of injective g(x)=g(y) and again using the definition of injective x=y therefore the composition of injective functions is injective.










    Ignore everything below
    But i'm not sure how to do like the general kind of proof.

    Like i know intuitively it is and i've tested a few but i'm not really sure how to prove it...

    I could do contraposition tho

    so

    P:=The composition of injective functions is injective
    Q:=An injective function
    ~Q:=Non-injective function


    i dunno


    direct proof?
    so if fog is injective then f and g are injective where f,g are in the set of ????

    I need some help
    Offline

    15
    ReputationRep:
    (Original post by will'o'wisp2)
    I have so far

    I claim that the composition of injective functions is injective. Recall that injective means that \forall x,y \in \mathbb R , f(x)=f(y) \Rightarrow x=y.
    Let f(g(x))=f(g(y)) then using the definition of injective g(x)=g(y) and again using the definition of injective x=y therefore the composition of injective functions is injective.










    Ignore everything below
    But i'm not sure how to do like the general kind of proof.

    Like i know intuitively it is and i've tested a few but i'm not really sure how to prove it...

    I could do contraposition tho

    so

    P:=The composition of injective functions is injective
    Q:=An injective function
    ~Q:=Non-injective function


    i dunno


    direct proof?
    so if fog is injective then f and g are injective where f,g are in the set of ????

    I need some help
    Yeah your proof is fine, I would just make the reasoning a bit more clear. You have g(x)=g(y) because f is injective and then you have x=y because g is injective.
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by B_9710)
    Yeah your proof is fine, I would just make the reasoning a bit more clear. You have g(x)=g(y) because f is injective and then you have x=y because g is injective.
    ok thanks
    Offline

    15
    ReputationRep:
    (Original post by will'o'wisp2)
    ok thanks
    I assume you'll also want to prove that composition of surjective functions is surjective.
    Also remember that you can extend these results to any finite number of compositions of injective/surjective functions.
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by B_9710)
    I assume you'll also want to prove that composition of surjective functions is surjective.
    Also remember that you can extend these results to any finite number of compositions of injective/surjective functions.
    woah there, hol up the master of prediction xD

    i can do an infinite regress with injective function but i'm not sure about surjective tho because the definition is slightly different but let me write up a rough answer of my injecive part and i'll take a look at the next one
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by B_9710)
    I assume you'll also want to prove that composition of surjective functions is surjective.
    Also remember that you can extend these results to any finite number of compositions of injective/surjective functions.
    so then

    I claim that the composition of surjective functions is surjective. Recall that to be surjective means that  if f:X\Rightarrow Y then \forall y \in Y\ \exists x \in X : f(x)=y
    on second thought the stuff below don't work

    I've tried a few examples and it seem that let's say f(x)=x and g(x)=x+1 if we do f(g(x))=x+1 then g(f(x))=x+1 , it seems that the "bigger" of the 2 surjecive functions always seems to be the surjective one, so it seems to me in this case for example f(g(x))=g(x) and g(f(x))=g(x) which is surjective hence the composite of both is surjective but i'm not really sure where else to go with this.
    Offline

    15
    ReputationRep:
    (Original post by will'o'wisp2)
    so then

    I claim that the composition of surjective functions is surjective. Recall that to be surjective means that  if f:X\rightarrow Y then \forall y \in Y\ \exists x \in X : f(x)=y
    on second thought the stuff below don't work

    I've tried a few examples and it seem that let's say f(x)=x and g(x)=x+1 if we do f(g(x))=x+1 then g(f(x))=x+1 , it seems that the "bigger" of the 2 surjecive functions always seems to be the surjective one, so it seems to me in this case for example f(g(x))=g(x) and g(f(x))=g(x) which is surjective hence the composite of both is surjective but i'm not really sure where else to go with this.
    I'm not sure what you're saying here.
    If you have  f:A\rightarrow B and  g:B\rightarrow C that are both surjective, we want to show that  g\circ f :A\rightarrow C is surjective.
    So basically we want to show that for all z in C there exists an x in A such that  (g\circ f )(x)=z .
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by B_9710)
    I'm not sure what you're saying here.
    If you have  f:A\rightarrow B and  g:B\rightarrow C that are both surjective, we want to show that  g\circ f :A\rightarrow C is surjective.
    So basically we want to show that for all z in C there exists an x in A such that  (g\circ f )(x)=z .
    i think i'll leave it there for today and come back tomorrow xD
    • Thread Starter
    Offline

    15
    ReputationRep:
    (Original post by B_9710)
    I'm not sure what you're saying here.
    If you have  f:A\rightarrow B and  g:B\rightarrow C that are both surjective, we want to show that  g\circ f :A\rightarrow C is surjective.
    So basically we want to show that for all z in C there exists an x in A such that  (g\circ f )(x)=z .
    I have returned lol.

    So i handed my questions in and i think for my answer. I put.

    \forall c \in C\ \exists\ b \in B\ :\ f(b)=c \Rightarrow \exists\ a \in A\ :\ g(a)=b

    I think that works? That was the main argument anyway. I think i'll be ok, thanks a bunch for you help as always
 
 
 
Poll
Cats or dogs?
Useful resources

Make your revision easier

Maths

Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

Equations

How to use LaTex

Writing equations the easy way

Student revising

Study habits of A* students

Top tips from students who have already aced their exams

Study Planner

Create your own Study Planner

Never miss a deadline again

Polling station sign

Thinking about a maths degree?

Chat with other maths applicants

Can you help? Study help unanswered threads

Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Write a reply...
Reply
Hide
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.